Vascular complications in diabetes mellitus: the role of endothelial dysfunction - Schalkwijk, Casper G.; Stehouwer, Coen D. A. (Clinical science (1979), 2005)
The endothelium is a complex organ with a multitude of properties essential for control of vascular functions. Dysfunction of the vascular endothelium is regarded as an important factor in the pathogenesis of diabetic micro- and macro-angiopathy. Endothelial dysfunction in Type I and II diabetes complicated by micro- or macro-albuminuria is generalized in that it affects many aspects of endothelial function and occurs not only in the kidney. The close linkage between microalbuminuria and endothelial dysfunction in diabetes is an attractive explanation for the fact that microalbuminuria is a risk marker for atherothrombosis. In Type I diabetes, endothelial dysfunction precedes and may cause diabetic microangiopathy, but it is not clear whether endothelial dysfunction is a feature of the diabetic state itself. In Type II diabetes, endothelial function is impaired from the onset of the disease and is strongly related to adverse outcomes. It is not clear whether impaired endothelial function is caused by hyperglycaemia or by other factors. Impaired endothelial function is closely associated with and may contribute to insulin resistance regardless of the presence of diabetes. Endothelial dysfunction in diabetes originates from three main sources. Hyperglycaemia and its immediate biochemical sequelae directly alter endothelial function or influence endothelial cell functioning indirectly by the synthesis of growth factors, cytokines and vasoactive agents in other cells. Finally, the components of the metabolic syndrome can impair endothelial function.